BRUXISM AMONG ATHLETES: A NARRATIVE REVIEW - Gałązka, Julia; Borek, Natalia; Miśkiewicz, Emilia; Krupa, Hanna; Stopa, Ewa; Wieczorek, Zofia; Kędrak, Magdalena; Stanisławski, Dominik; Jabłońska-Trzosek, Wiktoria; Pochwalski, Jakub; Gałązka, Kacper Jakub; Powierza, Emilia (International Journal of Innovative Technologies in Social Science, 2026)
Bruxism poses unique challenges for athletes due to heightened stress, anxiety, and performance demands that may exacerbate its prevalence and impacts. Aim: The aim of this study is to integrate evidence on prevalence, risk factors, impacts, diagnosis, and management strategies of bruxism among athletes. Materials and methods: Searches of PubMed, the Virtual Health Library, LIVIVO, and Google Scholar used a hybrid search strategy combining semantic and keyword-based retrieval methods. After screening 240 records, 27 studies met the eligibility criteria and were included in the narrative review. Results: The aggregated data reveals that athletes show a high prevalence of secondary bruxism, its primary aetiology being stress disorders fueled by the high-performance pressure and inadequate diagnosis and methods of management. Conclusions: Based on this narrative review it can be established that bruxism among athletes is primarily associated with stress disorders, categorising itself as secondary bruxism. The relationship between the prevalence of bruxism among athletes can be described as a positive feedback loop. The high stress environment to which athletes are exposed to pre-competition increases the likelihood of bruxism, while the risk factors of bruxism have a negative impact on performance, further increasing stress in this vicious cycle.